Pengaruh Elektroda pada Sambungan Las Baja Sa106 Grade A dengan Metode SMAW - Suherman, Suherman (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
AbstractThe welding joints of steel pipe used pressure vessels are required to have good quality joints so that they can accept pressure at high temperatures. The SA 106 Grade A carbon steel is always used as a superheater pipe in boilers because it has high strength and toughness, good weldability. The purpose of this study is to compare the mechanical properties of welding joints and the microstructure of the welding metals used difference type electrodes (E 6013 and E 7018) used in the welding of SA 106 grade A steel pipes with the SMAW method. The steel pipe made V dan used welding machine current type polarity DC (+) at welding current of 90 A. The coupon test is carried out several tests, namely tensile, bending, and hardness testing. The Observation of macrostructure and microstructure in the weld zone, HAZ, and parent material used microscope optic metallurgy. The results show the highest maximum of tensile strength obtained at the welded joint using the E7018 electrode. The impact strength of both types of welding electrodes has decreased when compared to the parent metal. The Macro-structure observations showed the presence of welding defects, namely the lack of fusion in the welding root and sidewall. The Microstructure in both welding metals is mainly acicular ferrite, grain boundary ferrite, and primary ferrite. The Impact toughness of the specimen with E6013 electrodes has decreased compared to the parent material.